The return from underperformance to sustainable world-class level: A case study of a male cross-country skier - Talsnes, R. K.; Moxnes, E. F.; Nystad, T.; Sandbakk, Ø. (Frontiers in Physiology, 2023)
Purpose: To determine the main factors associated with unexpected underperformance and prospectively describe the holistic process of returning to sustainable world-class level in a male cross-country skier.